2018
DOI: 10.1177/0145482x1811200609
|View full text |Cite
|
Sign up to set email alerts
|

Usability Evaluation of Tactile Map Symbols across Three Production Technologies

Abstract: Introduction Technological advances have introduced three-dimensional (3-D) printing as an option for creating tactile maps for people with visual impairments (that is, those who are blind or have low vision), diversifying the types of map products that are available. At the same time, it presents a challenge to map makers to implement designs across multiple production methods. We evaluated map symbols to determine their discriminability across three different materials: microcapsule paper, 3-D printer plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Graphic Tasks Participants Findings [1] Tactile graphic; HT condition: flat surface + hand tracking + smartwatch feedback (audio + vibration) Map Find labelled regions 12 BLV adults With filtering HT condition faster but without filtering slower; similar correctness; tactile and HT condition with filtering preferred [4] Tactile graphic (swell); tactile graphic (embossed); 3D model (printed)…”
Section: Appendix: Comparative Studiesmentioning
confidence: 99%
“…Graphic Tasks Participants Findings [1] Tactile graphic; HT condition: flat surface + hand tracking + smartwatch feedback (audio + vibration) Map Find labelled regions 12 BLV adults With filtering HT condition faster but without filtering slower; similar correctness; tactile and HT condition with filtering preferred [4] Tactile graphic (swell); tactile graphic (embossed); 3D model (printed)…”
Section: Appendix: Comparative Studiesmentioning
confidence: 99%
“…Arguably the most visible developments in tactile mapping over the past 19 years have been those regarding the media used to create and distribute tactile maps. While embossed paper remains a popular medium (Lobben, 2005), technological developments, including the proliferation of mobile computing (Poppinga et al, 2011), widespread Internet access (Ivanchev et al, 2014), and rapid prototyping (Brittell et al, 2018;Taylor et al, 2016) have had significant impacts on the landscape of tactile mapping research. These developments have had a democratizing effect on research, enabling a greater volume of experiments to be conducted by a greater diversity of scholars (especially those who may not have previously had access to the necessary resources 19 years ago).…”
Section: Production: Multimodalitymentioning
confidence: 99%
“…If 2002 was the year when we gazed at the digital horizon of tactile mapping, then 2021 may be a good time to assess exactly what is on the other side, how we got here, and where we need to go. On the whole, tactile mapping remains a 'specialist' field, with many papers noting that tactile maps are still expensive, hard to come by, difficult to make (Brittell et al, 2018;Ghodke et al, 2019;Stangl et al, 2019), and inherently unable to match the resolution of data that is possible with a visual map, even with the affordances granted by digital, interactive technologies ('Section 508', 2014;Weimer, 2017). Perhaps these are problems that will never quite be solved.…”
Section: Introductionmentioning
confidence: 99%
“…The current bottleneck for broader adaptation is the ability of caregivers (often non-technical individuals) to design and produce the maps for the end users. Furthermore, creation of tactile graphics, specifically maps, requires not only advanced technical skill and 3D design expertise but also an understanding of the tactile properties necessary to convey the sensory information to the user [3,4]. Although there are companies that offer tactile mapping services, they are costly, contain few encodings, and take a long time to produce and deliver [5].…”
Section: Introductionmentioning
confidence: 99%
“…The symbol set contained basic geometric shapes and was designed for microcapsule paper. Recently this symbol set has been used in 3D printed maps that were accepted well by users with blindness [3]. Other studies have explored 3D printing more representational or realistic symbols for use in exterior tactile maps [12] Additional studies have demonstrated the effectiveness of map reading using tactile icons for the blind [13].…”
Section: Introductionmentioning
confidence: 99%